Patient information regarding medical radiation exposure is inadequate: Patients' experience in a university hospital. Issue 4 (November 2017) - Ukkola, L.; Oikarinen, H.; Henner, A.; Haapea, M.; Tervonen, O.
Abstract: Introduction: It is suspected that little or no information is provided to patients regarding radiological examinations. The purpose was to evaluate the coverage, content and source of this information in a university hospital. Methods: Altogether 147 patients (18–85 years) were interviewed after different examinations using a questionnaire. The patients had undergone 35 low (<1 mSv), 66 medium (1–10), and 46 high (>10) dose examinations. They were asked if they were informed about radiation use, the course or indication of the examination, the consequences of not having the examination, other options, the dose and risks of radiation, the source for the information and if any consent was enquired. Results: 52 (35%) patients did not receive any information while 95 (65%) obtained some information. Fifty-six (38%) patients received an information letter, and 75 (51%) obtained oral information, mainly from the referrer or the radiographer. The information was mostly about indication, course or radiation use, very seldom about radiation risks and the other areas. Those with a nuclear medicine examination received information more often than those with other medium- or high-dose examinations (p = 0.004). The patients scored the received information as 2.2 (mean, SD 1.3) on a Likert scale from 1 (poor) to 5 (good). Conclusion: Patients obtained inadequate information regarding radiological examinations in a university hospital. The information was provided non-systematically from various sources. The results help to set up practical guidelines for systematic information and to follow up their efficiency. The mode of operation might be helpful elsewhere in the future. Highlights: Patients obtained inadequate information regarding medical radiation exposure. The information was provided non-systematically from various sources. Patients with nuclear examinations were informed better than with other modalities. In addition to general guidelines, practical information guidelines are needed.